Perancangan Sistem Informasi Inventaris Barang Berbasis Web pada PT Indobaja Karya Global - Virly Erasthi; Ishak Kholil (Jurnal Teknik dan Science, 2025)
The rapid advancement of information technology requires businesses to implement more effective resource and asset management. PT Indobaja Karya Global, a manufacturing and steel construction company, faces challenges in managing inventory manually. The lack of an integrated system has led to risks of recording errors, difficulties in stock monitoring, and insufficient detailed reporting. This study aims to design a web-based inventory information system to address these issues. A prototype method was used in the system development, involving stages such as listening to users, designing and building the prototype, and conducting testing. The results of the study show that the designed system improves efficiency and accuracy in inventory management, offering features that facilitate the recording and reporting process. With the web-based inventory information system, users can easily access inventory data and support better decision-making. The prototype development ensures the system aligns with user needs through feedback. This system also reduces manual errors and supports data integration for more structured management at PT Indobaja Karya Global.